Association of potassium and sodium parameters with the type of stroke: Importance of potassium and sodium in stroke - Yakar, Şule; Baykan, Necmi (Journal of Surgery and Medicine, 2024)
Background/Aim: Stroke is a significant cause of death along with malignant neoplasm and cardiovascular disease. Comorbidities and laboratory abnormalities are common in stroke patients. Imaging methods are the gold standard in the differential diagnoses of stroke, but they are not used sufficiently to diagnose stroke, especially in underdeveloped countries. In this study, we aimed to examine the association between electrolytes and clinical outcomes in patients with hemorrhagic and ischemic stroke. Methods: Patients diagnosed with a stroke in the emergency department for one year were reviewed for this retrospective cohort study. We separated the patients into two groups, hemorrhagic and ischemic stroke, according to their diagnosis. Demographic, clinical features, laboratory, and imaging results were compared for the two groups. Potassium and sodium variables and receiver operating characteristic (ROC) analysis were used to predict the stroke status of individuals. Results: In total, we included 321 patients in our study; 114 (35.5%) patients had experienced a hemorrhagic stroke, and 207 (64.5%) patients had had an ischemic stroke. In the hemorrhagic stroke group, 64% were males, while 50.2% of the ischemic stroke group were males. The most common chronic disease was found to be hypertension in both groups (42.1% (hemorrhagic) and 33.3% (ischemic)). There was a statistically significant difference in the comparison of potassium and sodium parameters and diagnostic groups (P=0.021 and P=0.036). In addition, hypokalemia was found to be significant in the diagnosis of hemorrhagic stroke (P<0.001). Conclusion: Using potassium levels in the differential diagnosis of ischemic and hemorrhagic stroke is especially useful in the management of patients who cannot undergo imaging.